Realistic texture synthesis for point-based fruitage phenotype - Yang, HuiJun; Chang, Jian; He, Dongjian; Geng, Nan; Wang, Meili; Zhang, JianJun; Jing, Xu; Chaudhry, Ehtzaz (Computers in biology and medicine, 2018)
Although current 3D scanner technology can acquire textural images from a point model, visible seams in the image, inconvenient data acquisition and occupancy of a large space during use are points of concern for outdoor fruit models. In this paper, an SPSDW (simplification and perception based subdivision followed by down-sampling weighted average) method is proposed to balance memory usage and texture synthesis quality using a crop fruit, such as apples, as a research subject for a point-based fruit model. First, the quadtree method is improved to make splitting more efficient, and a reasonable texton descriptor is defined to promote query efficiency. Then, the color perception feature is extracted from the image for all pixels. Next, an advanced sub-division scheme and down-sampling strategy are designed to optimize memory space. Finally, a weighted oversampling method is proposed for high-quality texture mixing. This experiment demonstrates that the SPSDW method preserves the mixed texture more realistically and smoothly and preserves color memory up to 94%, 84.7% and 85.7% better than the two-dimesional processing, truncating scalar quantitative and color vision model methods, respectively. •SPSDW algorithm for trade-off between visual quality and memory requirement.•Adaptive quadtree proposed to simplify texture and improve organization efficiency.•Perception-based subdivision and down sampling is developed to compress storage.•Proposed weighted oversampling scheme improved the fidelity of texture synthesis.